The C-terminal HSP90 inhibitor NCT-58 kills trastuzumab-resistant breast cancer stem-like cells - Soeun Park (Nature Publishing Group, 2021)
Abstract N-terminal HSP90 inhibitors in development have had issues arising from heat shock response (HSR) induction and off-target effects. We sought to investigate the capacity of NCT-58, a rationally-synthesized C-terminal HSP90 inhibitor, to kill trastuzumab-resistant HER2-positive breast cancer stem-like cells. NCT-58 does not induce the HSR due to its targeting of the C-terminal region and elicits anti-tumor activity via the simultaneous downregulation of HER family members as well as inhibition of Akt phosphorylation. NCT-58 kills the rapidly proliferating bulk tumor cells as well as the breast cancer stem-like population, coinciding with significant reductions in stem/progenitor markers and pluripotent transcription factors. NCT-58 treatment suppressed growth and angiogenesis in a trastuzumab-resistant xenograft model, concomitant with downregulation of ICD-HER2 and HSF-1/HSP70/HSP90. These findings warrant further investigation of NCT-58 to address trastuzumab resistance in heterogeneous HER2-positive cancers.